Younger age and induction failure predict outcomes in infant leukemia: 30 years of experience in a tertiary center - Ochoa-Fernández, Bárbara; Galán-Gómez, Víctor; Guerra-García, Pilar; Sanromán, Sonsoles; Martínez, Isabel; Bueno, David; Mozo, Yasmina; Sisinni, Luisa; Losantos, Itsaso; González, Berta; Pérez-Martínez, Antonio (Frontiers in Pediatrics, 2023)
Objectives This study aimed to evaluate the characteristics and outcomes of infant patients with leukemia. Methods A retrospective analysis was conducted in a cohort of 39 patients diagnosed with infant leukemia from 1990 to 2020 who underwent treatment at the pediatric hemato-oncology department of a tertiary hospital in Madrid, Spain. Results Of the 588 diagnosed cases of childhood leukemia, 39 (6.6%) cases were infant leukemia. The 5-year event-free survival and the 5-year overall survival were 43.6% (SE 4.1) and 46.5% (SD 24.08), respectively. In a univariate analysis, a younger age at diagnosis was associated with poorer outcomes (p = 0.027), as was induction failure (p = 0.0024). Patients treated with hematopoietic stem cell transplantation had better outcomes than non-transplanted patients (p = 0.001); however, the group comparisons that exclude patients who were unable to undergo transplantation due to refractoriness/relapse or death during treatment showed no significant differences. Conclusions The main risk factors that affected survival in our study were an age younger than 6 months and a poor response to induction therapy. It is important to identify poor prognostic factors in this population in order to seek different approaches that could improve outcomes.